Simulasi dan Pelatihan Tanggap Bencana dalam Upaya Mitigasi Bencana di Desa Santong, Kabupaten Lombok Utara - Karyawan, I Dewa Made Alit; I Wayan Yasa; Hasyim; Rohani; I Dewa Gede Jaya Negara; Eko Pradjoko; Humairo Saidah; Ida Ayu Oka Suwati Sideman; Made Mahendra (Universitas Mataram, 2025)
Santong Village, located in North Lombok Regency, has a high level of vulnerability to natural disasters such as strong winds, landslides, and earthquakes. The community’s limited understanding of these hazards increases the risk of casualties and material losses. This community service program aimed to enhance local disaster preparedness through community-based disaster response training and simulations. The activities were conducted in Santong Village on July 19, 2025. The methods included public awareness sessions, evacuation training, and disaster response simulations involving local residents and village officials. The results showed a significant improvement in participants’ understanding of disaster mitigation and evacuation procedures, along with a plan to establish a Village Disaster Response Team after the program. This initiative made a meaningful contribution to strengthening community capacity and supporting the realization of a Disaster-Resilient Village in Santong.